2013
DOI: 10.1002/ente.201300072
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antioxidants on the Cetane number, Viscosity, Oxidation Stability, and Thermal Properties of Biodiesel Produced from Nonedible Oils

Abstract: Poor oxidation stability of biodiesel is the central problem associated with its commercial acceptance. To enhance the practical feasibility of biodiesel, antioxidants are added to increase its storage stability. It is quite possible that these additives may affect other basic fuel properties of biodiesel. Therefore, the present study investigated the effects of antioxidants on the basic fuel properties of biodiesel produced from nonedible oils of African origin (Moringa oleifera, Jatropha curcus, and Croton m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…Anwar et al [10] report the significance in nutritional value and the use of M. oleifera in medicinal activities. The most eye-catching property of biodiesel derived from M. oleifera oil is the high cetane numbers of above 60, which are among the highest reported for a biodiesel fuel [11][12][13]. The details of origin, family and climatic condition for M. oleifera have been reported elsewhere in the literature [11,14].…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…Anwar et al [10] report the significance in nutritional value and the use of M. oleifera in medicinal activities. The most eye-catching property of biodiesel derived from M. oleifera oil is the high cetane numbers of above 60, which are among the highest reported for a biodiesel fuel [11][12][13]. The details of origin, family and climatic condition for M. oleifera have been reported elsewhere in the literature [11,14].…”
Section: Introductionmentioning
confidence: 90%
“…The antioxidants PY and PG were used in the present study as it was reported in our previous studies as the most effective antioxidants to increase the oxidation stability of COME and MOME [2,13]. Therefore, PY and PG were mixed in different concentrations (200-1000 ppm) in the COME and MOME samples.…”
Section: Sample Preparationmentioning
confidence: 98%
See 3 more Smart Citations